2000
DOI: 10.2754/avb200069010061
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Studies of Selected Ruminal and Blood Constituents in Dromedary Camels Affected by Various Diseases

Abstract: Baraka T. A., M. T. El-Sherif, A. A. Kubesy, J. Illek: Clinical Studies of Selected Ruminal And Blood Constituents in Dromedary Camels Affected by Various Diseases. Acta Vet. Brno 2000, 69: 61-68.Selected ruminal and blood constituents were investigated in a group of 81 dromedary camels affected by various diseases including simple indigestion (SI, n = 38), ruminal acidosis (RA, n = 19), frothy bloat (FB, n = 3), trypanosomiasis (TR, n = 11), caseous lymphadenitis (CL, n = 6), contagious skin necrosis (CSN, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 6 publications
(3 reference statements)
6
7
0
Order By: Relevance
“…Moreover, lowered values of iron during trypanosomiasis could be attributed to the decreasing of iron-transporting proteins that used by the parasite for its own growing and multiplication (Taylor et al, 2013). Significant increases in concentration of blood phosphorus among infected camels were showed in this study, which were compatible to that reported by (Baraka et al, 2000) and conflicted with (Schafer et al, 2011). However, it found that phosphorus is distributed in almost body organs, and play great function in production of adenosine triphosphate (ATP) especially in muscles.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, lowered values of iron during trypanosomiasis could be attributed to the decreasing of iron-transporting proteins that used by the parasite for its own growing and multiplication (Taylor et al, 2013). Significant increases in concentration of blood phosphorus among infected camels were showed in this study, which were compatible to that reported by (Baraka et al, 2000) and conflicted with (Schafer et al, 2011). However, it found that phosphorus is distributed in almost body organs, and play great function in production of adenosine triphosphate (ATP) especially in muscles.…”
Section: Discussionsupporting
confidence: 93%
“…However, the helminths are the major cause of impaired milk and meat production, decline in fertility of males and decrease in the calving rate of the females. The systematic studies of the disease conditions, particularly those caused by helminths in the camel, are few, and the published literature consists almost entirely of case reports, parasite records, and a few clinical trials of anthelmintic preparations long in use in other farm animals (Baraka et al 2000). This is probably due to the hostile environment in which the camel lives and the non-sedentary nature of the herds, constantly moving in search of grazing and water sources (Kohler-Rollefson 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These conditions could also have implications for rumination times, gut microbiota, and, finally, camel health ( 54 ). It is interesting to note that, according to Baraka et al ( 40 ), 23% of farmed camels suffer from ruminal acidosis associated with low ruminal pH. Camels, unlike other herbivores, are also predisposed to diabetes mellitus and high-caloric diets can compromise their welfare ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the current knowledge of the camel species, the proposed tool emphasized positive welfare states and human factors according to the Five Domains Model (49,50) and proposed indicators ad hoc for camels. Among the proposed welfare indicators, some were already validated in camels [e.g., BCS; (47)], others were selected based on their good feasibility, repeatability, and reliability demonstrated in other species (42,51) and the current knowledge of camel ethology, physiology, and pathology (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The proposed protocol assesses camel welfare applying a multidisciplinary approach (14,43), suggesting several indicators for each welfare principle assessed at three different levels, namely Caretaker, Herd, and Animal (Figure 1 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation